STUDY OF THE PREVENTIVE EFFECT OF ROYAL JELLY AGAINST THE HEPATOTOXICITY OF TWO ANTI-TUBERCULOSIS DRUGS - DJEMIL, RANDA; DJEMLI, SAMIR; DEROUICHE, FOUZIA; MAAMAR, HICHEM; ATI, SAMIA; ARROUF, DALEL; HOUGGAS, AHLAM; KHELLILI, KAMEL (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Aim: Hepatotoxicity is a well-known adverse effect during treatment with antituberculosis drugs, in particular the combination of rifampicin (RMP) and isoniazid (INH). Objective: The primary purpose of this study was to assess the contributory role of royal jelly decrease to in antituberculosis drug hepatotoxicity. Materials and Methods: This study is an experimental study in which the preventive effect of Royal jelly on isoniazid (INH), and rifampicin (RMP) hepatotoxicity is evaluated. In this study 21 male rabbit were randomly placed in three members groups including: control group, isoniazid and rifampicin and (isoniazid (INH), and rifampicin(RMP)) /royal jelly group. At the end of the study the laboratory criteria and histological features of liver toxicity were compared in different mentioned groups. Results: The treatment with isoniazid/ rifampicin led to Significant increase serum levels of liver enzymes, alkaline phosphate, alat and asat; and significant higher levels of albumin total proteins and Bilirubine, in compare to mixed isoniazid/ rifampicin / royal jelly also Group and the control. Whereas, the level of GSH concentration and enzymatic antioxidants SGSH-Px were decreased in the groups treatment by Isoniasid(INH), / rifampicin(RMP)comparative to the control grop but the MDA concentration is increased in this groups compared to addition of royal jelly are not present any significant change In addition, histological studies had not showed liver injury in isoniazid/rifampicin/ royal jelly group, while there was liver injury in isoniazid/ rifampicin alone group. Conclusion: The royal jelly, prevent the destructive effects of on the liver; probably because of its antioxidant properties.